Increasing Efficiency of Catering Enterprises through Modernization - Jamshedovna, Kurbanova Rakhima (International Journal of Psychosocial Rehabilitation, 2020)
The provision of public catering establishments with material and technical equipment plays an important role in the rapid development of this sector, especially in meeting the needs of the people. They differ in the type of interaction, size and level of services provided. However, not all of them meet the requirements of the period. Therefore, it is necessary to improve the technical and technological modernization of public catering establishments.The article develops a method for determining the technical and economic level of service in public catering establishments based on technical and functional indicators.